2022
DOI: 10.3390/toxics10020076
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects of Microplastics on Embryos and Observation of Toxicity Kinetics in Larvae of Grass Carp (Ctenopharyngodon idella)

Abstract: Microplastics have caused great concern in recent years. However, few studies have compared the toxicity of different sizes of microplastics in fishes, especially commercial fishes, which are more related to human health. In the present study, we revealed the effects of varying sizes of microplastics on grass carp embryos and larvae using scanning electron microscopy (SEM) and fluorescence imaging. Embryos were exposed to 80 nm and 8 μm microplastics at concentrations of 5, 15, and 45 mg/L. Toxicity kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…The most notable feature was that NIR-AIE-MNPs had strong emission at 1000 nm wavelength, which belonged to the second near-infrared (NIR-II) window (Figure D), thus enabling in vivo imaging at the NIR-II window. Usually, imaging in the visible range was accompanied by high tissue autofluorescence and background fluorescence, which led to observational artifacts in uptake and translocation studies of MNPs, as reported in fish and Daphnia . In contrast, our results showed almost no autofluorescence of zebrafish in the NIR-II window and can obtain high signal-to-background ratios in NIR images (maximum over 39 for NIR-AIE-MPs and 28 for NIR-AIE-NPs in this study) (Figures H and I). By comparison, the imaging of other commercial fluorescent PS particles was accompanied by the interference of strong biological autofluorescence, making it difficult to calculate the signal-to-background ratio due to the inability to clearly identify the boundaries of signal and background (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The most notable feature was that NIR-AIE-MNPs had strong emission at 1000 nm wavelength, which belonged to the second near-infrared (NIR-II) window (Figure D), thus enabling in vivo imaging at the NIR-II window. Usually, imaging in the visible range was accompanied by high tissue autofluorescence and background fluorescence, which led to observational artifacts in uptake and translocation studies of MNPs, as reported in fish and Daphnia . In contrast, our results showed almost no autofluorescence of zebrafish in the NIR-II window and can obtain high signal-to-background ratios in NIR images (maximum over 39 for NIR-AIE-MPs and 28 for NIR-AIE-NPs in this study) (Figures H and I). By comparison, the imaging of other commercial fluorescent PS particles was accompanied by the interference of strong biological autofluorescence, making it difficult to calculate the signal-to-background ratio due to the inability to clearly identify the boundaries of signal and background (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Such differences in water uptake and osmoregulation may influence MP ingestion. However, previous studies of MPs in fish have investigated either FW or marine species only [14][15][16] , thus the difference of MP ingestion in the two media was not clear because no reports have compared MP uptake in FW and SW using the same species.Here, we employed medaka (Oryzias) fishes to demonstrate differences in MP uptake in the two different media. Medaka are an attractive model fish for ecotoxicology studies because of their low rearing cost, high fertility, ease in rearing of embryos, abundant developmental information, and availability of a complete genome sequence [17][18][19][20][21] .…”
mentioning
confidence: 99%
“…Such differences in water uptake and osmoregulation may influence MP ingestion. However, previous studies of MPs in fish have investigated either FW or marine species only [14][15][16] , thus the difference of MP ingestion in the two media was not clear because no reports have compared MP uptake in FW and SW using the same species.…”
mentioning
confidence: 99%
“…The eight selected research papers can be grouped into three main themes: (1) the effects of microplastic exposure to aquatic biota (rotifers, mussels, fish larvae, and microalgae), encompassing 55% of the published papers in this SI [ 9 , 10 , 11 , 12 , 13 , 14 ]; (2) the distribution and seasonal variation of microplastics in aquatic environments [ 15 ]; and (3) the contaminants associated with microplastics in freshwater environments [ 16 ].…”
mentioning
confidence: 99%
“…As Guest Editors of this Special Issue, we were pleased to receive several papers concerning the interaction between microplastics and biota; despite a large number of peer-reviewed papers published on this research topic, there are still several gaps that need to be filled [ 17 , 18 ]. Zhang et al (2022) [ 12 ], for instance, investigated the toxicity of fluorescent nano- and microplastics (80 nm and 8 μm) on grass carp embryos and larvae using scanning electron microscopy (SEM) and fluorescence imaging. Their results showed that nanoplastics accumulated in the chorion and did not penetrate the embryo’s chorionic membrane.…”
mentioning
confidence: 99%